Cigarette Smoking, Reduction and Quit Attempts: Prevalence Among Veterans With Coronary Heart Disease - Shahoumian, Troy A. (Prev Chronic Dis, 2016)
INTRODUCTION: Cigarette smoking increases the risk of illness and early death for people with coronary heart disease. In 2010, Brown estimated prevalence rates for smoking among veterans and nonveterans with or without coronary heart disease in the United States, based on the 2003 through 2007 data from the Behavioral Risk Factor Surveillance System (BRFSS). Recent changes in BRFSS methods promise more accurate estimates for veterans. To inform assessment of efforts to reduce smoking, we sought to provide prevalence rates for smoking behaviors among US veterans with coronary heart disease and to compare rates for veterans with those for civilians. METHODS: We conducted a cross-sectional analysis of participants who responded to BRFSS from 2009 to 2012. Accounting for complex BRFSS sampling, we estimated national prevalence rates by sex for smoking status, frequency, and quit attempts; for those with and those without coronary heart disease; for civilians; for veterans and active duty personnel combined; and, after adjusting for BRFSS mingling of active duty personnel and veterans, for veterans only. We examined differences between veterans and civilians by using age-standardized national estimates. RESULTS: Among men with coronary heart disease, more veterans than civilians smoked and more were daily smokers, but veterans were no more likely to attempt to quit. Among women with coronary heart disease, we found no differences between civilians and veterans. CONCLUSION: Cigarette smoking is more prevalent among male veterans with coronary heart disease than among their civilian counterparts. Not distinguishing active duty personnel from veterans can materially affect prevalence estimates intended to apply solely to veterans.